Multimodal observational assessment of quality and productivity benefits from the implementation of wireless technology for out of hours working. Issue 2 (29th March 2012) - Blakey, John D; Guy, Debbie; Simpson, Carl; Fearn, Andrew; Cannaby, Sharon; Wilson, Petra; Shaw, Dominick
Abstract : Objectives: The authors investigated if a wireless system of call handling and task management for out of hours care could replace a standard pager-based system and improve markers of efficiency, patient safety and staff satisfaction. Design: Prospective assessment using both quantitative and qualitative methods, including interviews with staff, a standard satisfaction questionnaire, independent observation, data extraction from work logs and incident reporting systems and analysis of hospital committee reports. Setting: A large teaching hospital in the UK. Participants: Hospital at night co-ordinators, clinical support workers and junior doctors handling approximately 10 000 tasks requested out of hours per month. Outcome measures: Length of hospital stay, incidents reported, co-ordinator call logging activity, user satisfaction questionnaire, staff interviews. Results: Users were more satisfied with the new system (satisfaction score 62/90 vs 82/90, p=0.0080). With the new system over 70 h/week of co-ordinator time was released, and there were fewer untoward incidents related to handover and medical response (OR=0.30, p=0.02). Broad clinical measures (cardiac arrest calls for peri-arrest situations and length of hospital stay) improved significantly in the areas covered by the new system. Conclusions: The introduction of call handling software and mobile technology over a medical-grade wireless network improved staff satisfaction with the Hospital at Night system. Improvements in efficiency and information flow have been accompanied by a reduction in untoward incidents, length of stay and peri-arrest calls.